PENERAPAN DESAIN KELAS MODEL ‘’U’’ TERHADAP MOTIVASI BELAJAR MATEMATIKA DI UPT SD NEGERI 73 GRESIK KELAS IV - Muhammad Bayu Baharudin; Nataria Wahyuning Subayani; Arya Setya Nugraha (JUSEDA, 2022)
Learning motivation is something that can change the behavior of students for the better with the aim of obtaining maximum learning outcomes. Motivation is needed in ongoing learning activities, because motivation acts as a driving force in oneself that supports learning activities. Learning motivation can be said as an encouragement that makes a person take certain actions in order to achieve a goal, either internally or externally in the hope of obtaining complete learning outcomes which learning outcomes obtained above the KKM. However, there are still students who have low learning motivation. The arrangement of the "U" model class design is that all students can face to face and interact directly with the teacher, so that they will be more focused when learning takes place. The type of research that the author uses is a qualitative approach using descriptive analysis through field research which aims to describe how the influence of the U model class design on the motivation to learn mathematics on the material of square area. The technique in this research uses data collection techniques in the form of observation, interviews and documentation, while the data analysis in this study is data reduction, data presentation and conclusion drawing. The results of this study indicate that the influence of the U model class design is very influential on the learning motivation of students. This can be seen in the activities of students, which in this study some have been able to follow well. The teacher's activities at the time of the study were still unable to condition students in an orderly and uncluttered manner, but the teacher was able to apply the U model class design in learning. The difficulties experienced by students generally forget the material or do not understand and there are still students who find it difficult to focus when learning takes place.